Cholesteryl ester transfer protein (CETP) as a drug target for cardiovascular disease - Amand F. Schmidt (Nature Portfolio, 2021)
Despite being studied in clinical trials, CETP inhibitors are not yet an approved treatment for coronary heart disease. Here, by analyzing results from clinical trials and drug target mendelian randomization studies, the authors demonstrate that previous failure of CETP inhibitors are likely compound and not drug target-related.